Fungal-bacterial diversity and microbiome complexity predict ecosystem functioning - Wagg, Cameron; Schlaeppi, Klaus; Banerjee, Samiran; Kuramae, Eiko E.; van der Heijden, Marcel G. A. (Nature communications, 2019)
The soil microbiome is highly diverse and comprises up to one quarter of Earth’s diversity. Yet, how such a diverse and functionally complex microbiome influences ecosystem functioning remains unclear. Here we manipulated the soil microbiome in experimental grassland ecosystems and observed that microbiome diversity and microbial network complexity positively influenced multiple ecosystem functions related to nutrient cycling (e.g. multifunctionality). Grassland microcosms with poorly developed microbial networks and reduced microbial richness had the lowest multifunctionality due to fewer taxa present that support the same function (redundancy) and lower diversity of taxa that support different functions (reduced  functional uniqueness). Moreover, different microbial taxa explained different ecosystem functions pointing to the significance of functional diversity in microbial communities. These findings indicate the importance of microbial interactions within and among fungal and bacterial communities for enhancing ecosystem performance and demonstrate that the extinction of complex ecological associations belowground can impair ecosystem functioning. There is ongoing interest in linking soil microbial diversity to ecosystem function. Here the authors manipulate the diversity and composition of microbial communities and show that complex microbial networks contribute more to ecosystem multifunctionality than simpler or low-diversity networks.